PERANCANGAN MOTIF BATIK TULIS DENGAN INSPIRASI BENTUK VIRUS COVID 19 UNTUK PAKAIAN - Hanifah Ika Feriyana; Sarah Rum Handayani (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
The shape of the coronavirus can be arranged and mixed and matched into a new batik pattern and can attract people’s attention. In this project what was created was a batik pattern with the main motive of the coronavirus. During the pandemic, many new motive ideas emerged, one of which was the form of the coronavirus. The method of creation in this final project uses the method of art creation SP. Gustami consists of three stages. The stages are exploration, design, and realization. The motive that appears in the batik is a new form of the coronavirus which is arranged in such a way that it can produce the latest motive. The design of written batik motive with the coronavirus motif is designed with the intent and purpose of providing new innovations with a variety of motives from various forms of the coronavirus into a complex whole with Indonesian local wisdom. Creating batik cloth products with the characteristic motive that can reflect a commitment to local art.